The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1536/ihj.47.867
|View full text |Cite
|
Sign up to set email alerts
|

Association of Decreased Variation of R-R Interval and Elevated Serum C-Reactive Protein Level in a General Population in Japan

Abstract: SUMMARYSeveral studies have suggested that an increased high sensitivity C-reactive protein (hsCRP) level is a strong independent predictor of increased risk for atherosclerotic cardiovascular mortality and morbidity. Reduced heart rate variability (HRV) has also been reported to predict cardiovascular events such as sudden death and myocardial infarction in apparently healthy subjects. The aim of this cross-sectional study was to test the possible correlation between variation of the R-R interval as one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 38 publications
3
21
0
3
Order By: Relevance
“…Other studies have also shown an association between parasympathetic activity and inflammation (37), providing a possible mechanistic explanation for our study's results. However, treatments used in cardiac patients, such as β blockers, angiotensin-converting enzyme (ACE) inhibitors and angiotensin receptor blockers, have been shown to augment parasympathetic activity and reduce inflammation as part of their beneficial mechanisms (38)(39)(40).…”
Section: Discussionsupporting
confidence: 84%
“…Other studies have also shown an association between parasympathetic activity and inflammation (37), providing a possible mechanistic explanation for our study's results. However, treatments used in cardiac patients, such as β blockers, angiotensin-converting enzyme (ACE) inhibitors and angiotensin receptor blockers, have been shown to augment parasympathetic activity and reduce inflammation as part of their beneficial mechanisms (38)(39)(40).…”
Section: Discussionsupporting
confidence: 84%
“…Findings differed across these studies. While two investigations reported a significant inverse relationship with the inflammatory markers CRP and IL-6, one study demonstrated higher CRP levels only in the group of the lowest HRV quartile (Kon et al, 2006). The remaining group tested inflammatory markers and HRV during and after a mental stress test and found no relationship between immune responses and heart rate variability (Owen and Steptoe, 2003).…”
Section: Resultsmentioning
confidence: 98%
“…The effect of vagal activity was mainly studied on Interleukin-6 (IL-6) and C-reactive peptide (CRP). Six studies reported on subjects with known or suspected coronary heart disease (CHD) (Hamaad et al, 2005; Lanza et al, 2006; Madsen et al, 2007; Nolan et al, 2007; Psychari et al, 2007; Yue et al, 2007), four studies investigated the association of HRV and inflammation in healthy population (Owen and Steptoe, 2003; Sajadieh et al, 2004; Kon et al, 2006; Sloan et al, 2007). Two papers analyzed inflammatory markers and HRV in metabolic syndrome and impaired glucose tolerance, respectively (Brunner et al, 2002; Diakakis et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…(Int Heart J 2008; 49: 175-181) Key words: Cardiac autonomic function, Heart rate variability, Short-term, Long term, Workers HEART rate variability (HRV) is a physiological maker used to assess the autonomic nervous system (ANS) and is significantly associated with a variety of pathologies, such as cardiovascular disease and diabetes mellitus. [1][2][3][4][5][6] The HRV can be assessed over the short (usually 5-15 minutes) or long (24 hours) term. Long-term measurements reflect the overall change in the heart rate under nonspecific, changing conditions because the subjects perform their usual daily activities during the test.…”
Section: Discussionmentioning
confidence: 99%